Lower-back discomfort and ergonomic hazards among artisanal fishermen in Tamil Nadu, India: a cross-sectional study (International Journal of Occupational Safety and Health, 2026)
Introduction: Lower back discomfort is a prevalent occupational health issue among fishermen, substantially contributing to disability adjusted life years and reduced work performance. The primary aim of the study is to examine the lower back discomfort, occupational profile, ergonomic hazard exposure and overall health and wellbeing among artisanal fishermen.Methods: :   The present study has been conducted among 400 randomly selected artisanal fishermen from coastal villages of Ramanathapuram District, Tamil Nadu, India between February 2024 and April 2025. Data has been collected using a pretested interview schedule, the standardized Nordic Musculoskeletal Questionnaire (2007), Perceive Stress Scale – 10 and adapted Workplace health and safety survey. Descriptive statistics, Spearmen correlation and regression have also been performed.Results: Among the selected 400 artisanal fishermen, 269(64%) reported lower back discomfort in the past 12 months with 68(22%) have experienced interference in daily activities. Ergonomic hazards including lifting of heavy weights 172(64%), repetitive movements 252 (91%), improper working postures 78 (29%) and prolonged standing (>2 hours) 105(39%) have been significantly associated with Lower Back Discomfort. With frequent lifting showing adjusted odds ratios of 7.7 (always) and 6.4 (often), psychosocial factors such as poor sleep quality (aOR = 3.6), moderate perceived stress (aOR = 2) and alcohol consumption (22%, p